Diagnostic Performance of Red Blood Cell Indices in the Differential Diagnosis of Iron Deficiency Anemia and the Thalassemia Trait in Chile: A Retrospective Study - Mario Balcázar-Villarroel; Angélica Mancilla-Uribe; Sandra Navia-León; Florencia Carmine; Katherine Birditt; Cristian Sandoval (Diagnostics)
Background: Iron deficiency anemia (IDA) and the β-thalassemia trait (BTT) are two main causes of hypochromic–microcytic anemia worldwide. Researchers have described many red blood cell (RBC) indices as screening tests for presumptive differentiation, based on differences observed in complete blood count (CBC) data for each condition. There are few BTT reports in Chile, and neither laboratories nor clinical staff have widely used these indices. Objective: The objective of this study was to evaluate the diagnostic performance of 29 RBC indices in 182 patients (51 BTT and 131 IDA) and compare CBC results in both groups. Methods: A retrospective search was carried out in the Laboratory Information System between January 2021 and February 2024 to collect results from CBC, and 29 RBC indices were calculated for each patient. Then, sensitivity, specificity, positive predictive value, negative predictive value, Youden’s index, positive likelihood ratio, negative likelihood ratio, and diagnostic accuracy were calculated using MedCalc©. Results: The Green and King, Wongprachum, and Keikhaei indices showed the best discriminatory power with Youden index values of 0.923, 0.908, and 0.896, respectively, and significant differences were observed in all CBC parameters between BTT and IDA patients (p < 0.001). Conclusions: The Green and King, Wongprachum, and Keikhaei indices showed the best performance; therefore, they can be used as screening for the differential diagnosis between BTT and IDA in order to improve diagnosis given the important therapeutic and epidemiological implications. In this way, clinical laboratories could have a main role in the investigation of these patients.